ANALISIS KOMPETENSI GURU DALAM PENGUASAAN TEKNOLOGI INFORMASI DAN KOMUNIKASI PADA PEMBELAJARAN DI SEKOLAH DASAR NEGERI 2 PURBALINGGA LOR - Sahid Zuhdi Adz Dzaky; Badarudin Badarudin; Aji Heru Muslim (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2020)
This research focuses on teacher competencies in the use and utilization of information and communication technology in learning. The purpose is to analyze and describe teacher competencies in the use of information and communication technology in learning in a school. The study was conducted using a qualitative descriptive approach. This research was conducted using observation through direct interviews with informants consisting of school principals, class teachers and students. Data validity uses triangulation and reflection. The results show that teachers at SDN 02 Purbalingga Lor have been able and able to use, utilize and collaborate information and communication technology with learning in the classroom. Although in addition there are also constraints both internal and external. Support from related agencies was immediately felt both by the students and by the teachers as users. Principals with their full support also continue to encourage teachers to always innovate, especially in the use of information and communication technology in learning, both in the classroom and outside the classroom.Keywords: Teacher competence, information and communication technology, elementary school.